Development and Validation of Stereoselective Method for the Quantification of Stereoisomers of Eliglustat Using Amylose-Based Immobilized Chiral Stationary Phase (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: The main aim of the present work is to develop and validate a new simpler, selective, specific, and robusthigh performance liquid chromatographic method for the separation of Eliglustat and its isomers. Materials andMethods: For the accurate quantification method, for the all isomers was developed by performing the significantnumber of methods on trial and error techniques using a large number of polar and non-polar solvent mixturesas mobile phase. A distinctive resolution between Eliglustat and its stereo isomers was achieved on ImmobilizedAmylose tris (3-chloro-4-methylphenylcarbamate) stationary phase namely CHIRALPAK IF-3(4.6 mm ×250 mm, 3 μm), with flow rate of 1.0 mL/min using isocratic method containing n-Hexane/Ethanol/Methanol/Diethyl amine (90/05/05/0.1,v/v/v/v). Column temperature was maintained at 40°C and detection wavelengthof 280 nm. Results and Discussion: The limit of detection and limit of quantification values of Eliglustat S,SIsomer,R,S-Isomer, and S,R-Isomers were found to be 0.0027/0.0082, 0.0367/0.1112, and 0.0375/0.1137 μg/mL,respectively. The method was found to be precise, accurate, and linear (R2 > 0.999). Recoveries of all isomerswere found to be in the range of 90–110%. Conclusion: As per the ICH guidelines, the developed method hasbeen shown to be linear, accurate, precise, robust, and sensitive. The method is also considered quality controlfriendly as it is robust, uses isocratic mobile phase and employs commonly used solvents as mobile phase.